If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying logx + 3 + logx = 1 Reorder the terms: 3 + glox + glox = 1 Combine like terms: glox + glox = 2glox 3 + 2glox = 1 Solving 3 + 2glox = 1 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2glox = 1 + -3 Combine like terms: 3 + -3 = 0 0 + 2glox = 1 + -3 2glox = 1 + -3 Combine like terms: 1 + -3 = -2 2glox = -2 Divide each side by '2lox'. g = -1l-1o-1x-1 Simplifying g = -1l-1o-1x-1
| 18=2y-12 | | 7x+4(0)=-11 | | 3w+6.5=6.5-2w | | -4b-6-5=13 | | Z+5z-24= | | n+5.9=6.1 | | 2x-7=2x+9 | | n+1+3n=1 | | .08x+.06(x+12)=7.7 | | 1.3x+2.7x=14.5-2.5 | | 24x^2-6x-45= | | x+2+x+3=4x | | 8.6x51/4 | | 18x-360=90 | | 5m+6m=-11 | | d-2=17 | | -8=(-9x-17)/10 | | -2=1-5x+2 | | [0.5n]+17+n=20 | | 0.06(y-3)+0.10y=0.20y-0.01(50) | | 2w+3.5*2+2w=22 | | 3(x^2+3x-4)=0 | | 1.3+2.7x=14.5-2.5 | | 6=k+6-6 | | 2x+11=28 | | .65x-10=15 | | 12x+8=7x+48 | | 6x+3-1=-16 | | 28=y/4-9 | | 15=-3(-1)+9 | | =2(9+5k) | | -8=-9x-17/10 |